Physiological seeds quality of murta (Blepharocalyx salicifolius (Kunth) O. Berg – Myrtaceae) and viability during storage - Calil, Anaise Costa (2008)
Tree of small until great size, murta is originary of the South of Brazil, Uruguay, Argentina and Paraguay. To evaluate the physiological quality of seeds lots collected in Gramado, Farroupilha and Barra do Ribeiro districts, at Rio Grande do Sul state, a study was carried out at Porto Alegre Botanical Garden Seeds Laboratory. Seeds evaluations were conducted at harvest time and each 30 days, during four months, through germination and seedlings emergence tests, beginning and mean time of germination, beginning and mean time of seedlings emergence determinations. The seeds from Barra do Ribeiro district presented higher physiological quality at harvest time and during storage. During four months of storage, the seed lots of Farroupilha and Barra do Ribeiro districts presented no significantly difference in viability, which indicates that B. salicifolius seeds present, at least, a four months longevity period in cold chamber.